DISPARITY OF CRIMINAL DECISIONS IN CORRUPTION CASES IN INDONESIA - Mahali, M. Ubab Sohibul; Hanim, Lathifah (Jurnal Hukum Khaira Ummah, 2024)
The purpose of this study is to determine and analyze the Disparity of Sentencing Decisions in Corruption Crimes in Indonesia, to determine and analyze the weaknesses of the disparity of sentencing decisions in corruption cases and their solutions. This thesis uses a normative legal approach method, the research specifications are descriptive analysis, data sources consist of secondary data taken from primary legal materials, secondary legal materials, tertiary legal materials, data collection techniques through literature studies. The results of the study show that disparities in sentencing are still often seen in monitoring trials throughout 2023. The effectiveness of Supreme Court Regulation Number 1 of 2020 has also not been maximized. The weaknesses of the disparity of sentencing decisions in corruption cases are influenced by the weaknesses of the legal structure, namely the positivistic mindset of judges and the second is the non-positivistic mindset of judges. The mindset of judges with a positivistic character places great emphasis on formal text measurements in exploring legal truth, while a non-positivistic mindset can elaborate legal texts with socio-legal contexts in exploring legal truth. The weakness of the legal substance is that the Supreme Court's efforts to avoid disparities in criminal penalties for corruption crimes stipulated in Supreme Court Regulation Number 1 of 2020 concerning the Guidelines for Sentencing Article 2 and Article 3 of the PTPK Law are not accompanied by adjustments to laws and regulations such as the Criminal Code and Criminal Procedure Code. Weaknesses of Legal Culture where there are three cultural aspects that can facilitate corruption, namely family culture, paternalistic societal orientation, and a societal culture that is less courageous to be frank (non-assertive). The solution to these obstacles is based on the empirical reality that the handling of corruption cases by judges has experienced a lot of decline and failure to present laws that are fair, beneficial and protect the interests of society. The mindset of judges with a positivistic character needs to be reorganized based on a new, progressive mindset in deciding various legal problems that have emerged recently which are increasingly complex and complicated, especially in deciding corruption cases. Judge education at all levels and court environments needs to be improved so that judges are able to solve various legal problems appropriately, fairly and wisely. Progressive legal content needs to be elaborated in the education of prospective judges and legal education institutions in general.